To Lobby or to Partner? Investigating the Shifting Political Strategies of Biopharmaceutical Industry Associations in Innovation Systems of South Africa and India. (February 2016) - Papaioannou, Theo; Watkins, Andrew; Mugwagwa, Julius; Kale, Dinar
Summary: The role of industry associations in shaping policy through various lobbying activities is well established. In most cases, while such activities are deemed essential from an industry perspective, they also carry negative connotations connected to narrow rent-seeking and the pursuit of elites' interests which run counter to the public good and discourage competition and subsequent innovation. As such, industry associations have long been excluded from discussions regarding the relational dynamics and evolution of innovation systems. In contrast, this paper builds upon more recent work that places industry associations as key intermediary actors that facilitate knowledge exchange and institutional capacity building, particularly in the context of developing countries where limited institutional capacities and substantial knowledge gaps can limit both innovation and development. Employing a qualitative cross-national comparison, this paper examines the changing roles and activities of biopharmaceutical industry associations in the development of the South African and Indian pharmaceutical industries, with a particular focus on government–industry relations. For doing so, the paper captures developments during three main periods through which both the South African and Indian biopharmaceutical industries have similarly evolved, although within different national contexts: (1) pre-liberalization, (2) expanding pluralism, and (3) increasing partnership. We argue that in South Africa and India, particular historical trajectories and lack of institutional capacities are shifting industry associations away from ineffective lobbying to a new political approach that emphasizes partnering with government in the pursuit of not only narrow industry objectives, but also broader development aims.